Changes of physical properties of glass surfaces exposed to KNO3 vapors - Saggioro, B. Z.; Ziemath, E. C. (Elsevier B.V., 2006)
Modifications of glass surfaces were studied after exposure of samples to an atmosphere resulting from the decomposition of molten KNO3. The diffusion coefficient of K+ ions migrating into the surfaces of float glass and synthesized glasses doped with up to 5 wt% SnO2 was calculated by the Boltzmann-Matano technique. The Vickers hardness and the refractive index increase with exposure time. Infrared spectra show that the migration of K+ is responsible for an increase in the number of non-bridging oxygens in the exposed samples. The spectra of the synthesized glasses present evidences that their surfaces undergo crystallization during the exposure. All results lead to the conclusion that the presence of tin in the glasses hinders the diffusion of K+ ions, thus affecting the Vickers hardness, the refractive index and the infrared spectra. It is shown that the exposure method can be used as an alternative process to promote the K+ migration into glass surfaces. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ion exchange; hardness; FTIR measurements; surfaces and interfaces